The advantage of experienced start-up founders in venture capital acquisition: evidence from serial entrepreneurs - Junfu Zhang (Institute for the Study of Labor (IZA), 2007)
Existing literature suggests that entrepreneurs with prior firm-founding experience have more skills and social connections than novice entrepreneurs. Such skills and social connections could give experienced founders some advantage in the process of raising venture capital. This paper uses a large database of venture-backed companies and their founders to examine experienced founders' access to venture capital. Compared to novice entrepreneurs, entrepreneurs with venture-backed founding experience tend to raise more venture capital at an early round of financing and tend to complete the early round much more quickly. In contrast, experienced founders whose earlier firms were not venture-backed do not show a similar advantage over novice entrepreneurs, suggesting the importance of connections with venture capitalists in the early stage of venture capital financing. However, when the analysis also takes into account later rounds of financing, all entrepreneurs with prior founding experience appear to raise more venture capital. This implies that skills acquired from any previous founding experience can make an entrepreneur perform better and in turn attract more venture capital.
Keywords: 330; Unternehmensgründung; Unternehmer; Berufserfahrung; Risikokapital; Verschuldungsrestriktion; USA